A Spectrophotometric Flow Injection Method for Determination of Ultratrace Amounts of Phenylhydrazine by Its Inhibition Effect on the Reaction of Thionin and Nitrite - M. Keyvanfard; Kh. Alizad (Journal of Chemistry)
A simple flow injection colorimetric procedure for determining phenylhydrazine was established. It is based on the reaction of phenylhydrazine in sulfuric acid with thionin and sodium nitrite. Reaction was monitored spectrophotometrically by measuring thionin absorbance at λmax=602 nm. A standard or sample solution was injected into the sulfuric acid stream, which was then merged with sodium nitrite stream and thionin stream. Optimum conditions for determining phenylhydrazine were investigated by univariate method. Under the optimum conditions, a linear calibration graph was obtained over the range 0.05–0.60 μmol L−1, and the detection limit was 0.027 μmol L−1(s/n=3). The proposed method has been satisfactorily applied to the determination of phenylhydrazine in human serum and water samples.